Penegakan Hukum terhadap Pelanggaran Lalu Lintas di Kota Jambi Melalui Tilang Elektronik Atau Electronic Traffic Law Enforcement (ETLE) - Alvarie Norindra Leonita; Islah Islah; Hisbah Hisbah (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to identify and analyze and criticize law enforcement against traffic violations in the city of Jambi through electronic tickets or ETLE and criticize the obstacles to law enforcement against traffic violations in the city of Jambi through electronic tickets or ETLE and criticize the efforts to overcome the obstacles faced. in law enforcement against traffic violations in the city of Jambi through electronic ticket or ETLE. This research method is empirical juridical. The result of the research is that law enforcement against traffic violations in the city of Jambi through Electronic Traffic Law Enforcement (ETLE) based on Law Number 22 of 2009 concerning Road Traffic and Transportation has been carried out well but has not been effective. There are 2 (two) obstacles in law enforcement against traffic violations in the city of Jambi through electronic tickets or Electronic Traffic Law Enforcement (ETLE), namely the address of the violator of traffic signs does not match the address based on the Vehicle Number Certificate and Closed Circuit Television (CCTV) does not function optimally. Law enforcement efforts against traffic violations in the city of Jambi through electronic traffic tickets or Electronic Traffic Law Enforcement (ETLE), namely providing clarity on the 2018 SOPs or which serve as guidelines for all officers in the practice of implementing the e-ticketing system, providing intense socialization to the community and providing services. call center, coordinate with the local court to be able to include a table of fines for officers and carry out mental development of traffic order in early childhood through the Polsanak program (the police are friends with children) at school.